Execution of Ijarah Contracts in Rental Houses According to an Islamic Economic Perspective: Case Study of Rental Houses in Bengkalis City - Zulfikar Hasan; Khozinatul Asrori (Westscience Press, 2023)
The implementation of Ijarah Rental Contracts at Hendrawan's Boys/Girls Boarding House in Islamic Economics is the primary focus of this study. The purpose of this study was to ascertain how the rental of boarding houses would be implemented in Sengoro Village, Bengkalis District. Additionally, determine whether the ijarah contract's execution is hindered. The methodology of this study is qualitative. Qualitative research is the term for this kind of study. Field conditions and descriptions serve as the basis for this type of research, which aims to develop concepts, understandings, and theories. A study that aims to accurately describe the nature of an individual, condition, symptom, or particular group as it is is known as descriptive analysis. An interview or interview is the method used to collect data. An interview is a kind of conversation that uses verbal communication to get information and written documentation. The rent agreement for renting Hendrawan's son and daughter's boarding house is carried out verbally as a result of this research. The rental contract system can be transferred as long as the owner of the boarding house has given prior approval, proof of payment is only recorded via WhatsApp, and the tenant is entirely responsible for the provided boarding facilities. The study came to the conclusion that the rental house's ijarah contract was carried out in accordance with Islamic law. However, the boarding house owner's income decreased as a result of the Covid-19 pandemic's obstacles.